LEGAL ASPECTS OF TITLE INSURANCE AS AN ELEMENT OF PUBLIC SAFETY IN THE IMPLEMENTATION OF REAL ESTATE TRANSACTIONS - Zaiets, Olexandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The problem of safety during the implementation of property transactions is all stronger integrated in adjusting of property relations, what their doubtfulness and mistrust cause to them. Property rights and financial risk of loss or limitation of right of ownership for the object of the real estate title insurance is called to secure. A reliable economical and legal instrument which is functioning successfully in the world leading countries and protecting the rights of market relations subject is title insurance.